Estudo comparativo dos efeitos dos óleos essenciais de Cymbopogon citratus e Cymbopogon winterianus (POACEAE) no sistema nervoso central de camundongos - Silva, Monalisa Ribeiro (2009)
The main objective of the present work was to study in a comparative manner the effect of two essential oils, isolated from the leaves of Cymbopogon citratus (Cc) and Cymbopogon winterianus (Cw), medicinal herbs that belong to the Poaceae family and are common to the Northeast Region of Brazil. Their EOs effects were studied on the mice central nervous system (CNS). For that mice from both sexes (25 g) were acutely treated with the doses of 25, 50, 100 and 200 mg/kg, i.p., and submitted to the tests of chemically induced convulsions (pilocarpine, PTZ and strychnine-induced convulsions), barbiturate-induce sleeping time (to evaluate sedative actions), open field and rota rod (to evaluate locomotor activity and motor coordination), plus maze and forced swimming tests (to assess anxiolytic and antidepressant activities respectively). The results showed that in the model of pilocarpine-induced convulsions the effects in males were more prominent with Cc (200 mg/kg) that increased the latency to the 1st convulsion (2.2 times) and the latency to death (3.9) as compared to controls. In females a greater effect was observed with Cw (200 mg/kg) on the latency to death (3.9 increase). Both EO were more efficacious on the PTZ-induced convulsion model, increasing in males the latency to the 1st convulsion in 5.9 (Cc) and 2.9 (Cw) and in 15.6 (Cc) and 21.1 (Cw) times the latency to death. Similar, but lower effects were seen in females. Interestingly, only Cw was somehow more effective on the strychnine-induced convulsions and effects were mainly on the latency to death. Both EOs significantly decreased the latency time to sleep and sleep duration in the barbiturate-induced sleeping time test, indicative of sedative action. The drug`s effect in this last parameter was dose-dependent and Cw was somehow more potent. The EOs decreased the locomotor activity mainly at their highest doses, which also lead to falls, as assessed by the open field and rota rod tests, respectively. Unless for the decrease in the number of entrance in the open arms with higher doses no other effects were detected in the elevated plus maze test used for the evaluation of anxyolytic effects. The CNS depressant effects of both EOs were further confirmed by the forced swimming test where the EOs, unlikely imipramine used as the reference drug, increased the immobility time. In tests in vitro Cc and Cw drastically decreased the myeloperoxidase MPO (a biomarker for inflammation) release from human neutrophils suggesting a potent anti-inflammatory action at doses as low as 0.01 µg/ml. However, neither of the EOs present any radical scavenging activity in the DPPH assay. All together the results showed that the EOs of Cc and Cw present indeed sedative and hypnotic effects and at the range of doses used are potent CNS depressant drugs, making them potentially useful drugs, especially as sedative and hypnotic. Besides, some of their effects such as the anticonvulsant one seems to associated to a GABAergic action similar to that of a DZP-type compound.